Student Errors In Solving Story Problems With Fraction Count Operations; Analysis On Class VII Students - Kristin Alviane Friskila Pomantow; Rosiah J. Pulukadang; Ichdar Domu (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
. Fraction is one of the materials in mathematics subject in class VII odd semester, which students must master well. Because this material continues from elementary school. Fraction is related to every day, and many problems use the concept of fractions. The research aims to describe the errors according to Newman's procedure, which students carry out to solve the issues. The methods used in data collection were tests and interviews. The written examination was given to class VII 15 students as the subject. The test questions consist of 4 item description questions, then from the results of the written test of 5 students who made mistakes according to the Newman procedure. The results of research that have been carried out on students according to Newman's approach in solving fractions questions as indicated by the results of their daily tests, the most frequent error is the process skill error and encoding error with a percentage of 58,33%, the transformation error is 51,66%, comprehension error 41,66% and the last percentage of reading error 25 %. The causes of student errors include being unable to read correctly, not understanding fractions, and being unable to determine the formula or steps to use, such as making mistakes in the calculation process and writing wrong information or answers.